Overview of Air Microbiological Quality at The Microbiology Laboratory at Campus III Poltekkes Kemenkes Surakarta - Makhabbah Jamilatun (CV. Ulil Albab Corp, 2022)
Indoor air quality is a problem that needs attention because it will affect human health. A laboratory is a place for a group of people who carry out various kinds of activities, both practicum, research, observation, training, and scientific testing. In the laboratory room where there is microbial contamination that can cause disease and can be transmitted through equipment, materials used, laboratory and research samples, and laboratory visitors. This research was conducted to know the description of the quality of air microbiology at the Microbiology Laboratory Campus III Poltekkes Kemenkes Surakarta. The study began with the isolation of air microbes in the Microbiology Laboratory of Campus III Poltekkes Kemenkes Surakarta with PCA (Plate Count Agar) media, continued with colony counting and macroscopic observations of the colony characteristics found. Microbes were found in the air at a predetermined air intake point. There were 4 colonies of air in the instructor's workroom, 19 colonies of air in the laboratory, 1 colony of air in the laboratory equipment and materials storage room, 16 colonies of air outside the laboratory, 13 colonies of air near the laboratory bathroom. At the five sampling points, the number of microbial colonies still met the standard. However, the presence of microbes in the air needs attention, because indoor air quality can affect human health.